2014
DOI: 10.2967/jnumed.114.140228
|View full text |Cite
|
Sign up to set email alerts
|

Individual-Reader Diagnostic Performance and Between-Reader Agreement in Assessment of Subjects with Parkinsonian Syndrome or Dementia Using 123I-Ioflupane Injection (DaTscan) Imaging

Abstract: Establishing an early, accurate diagnosis is fundamental for appropriate clinical management of patients with movement disorders or dementia. Ioflupane 123 I Injection (DaTscan, 123 I-ioflupane) is an important adjunct to support the clinical diagnosis. Understanding individualreader diagnostic performance of 123 I-ioflupane in a variety of clinical scenarios is essential. Methods: Sensitivity, specificity, interreader, and intrareader data from 5 multicenter clinical studies were reviewed. The different study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…among all readers and thus the k-values. These results are in agreement with those of other 123 I-ioflupane SPECT and amyloid brain PET studies, which also showed that high k-values for both intraobserver and interobserver agreements (14,(23)(24)(25)(26) improved as quantitative data were provided to readers (14,26).…”
Section: Discussionsupporting
confidence: 91%
“…among all readers and thus the k-values. These results are in agreement with those of other 123 I-ioflupane SPECT and amyloid brain PET studies, which also showed that high k-values for both intraobserver and interobserver agreements (14,(23)(24)(25)(26) improved as quantitative data were provided to readers (14,26).…”
Section: Discussionsupporting
confidence: 91%
“…Seibyl et al . 2014). This reflects the greater difficulty in rating subjects whose scans are at an earlier disease stage and where more, therefore, have borderline abnormal scans.…”
Section: Discussionmentioning
confidence: 99%
“…All images were visually interpreted as either positive or negative for DAT or VMAT‐2 deficit25 by two experienced, independent nuclear medicine readers blinded to clinical diagnosis. Visual interpretation for both DAT and VMAT‐2 images required the reader to interrogate the intensity and symmetry of radiotracer uptake in left and right putamen to determine whether the pattern was consistent with a dopaminergic deficit.…”
Section: Methodsmentioning
confidence: 99%